The Role of Independent Value Creation, Value, and Trust on Banking Marketing Performance: Moderating Role of Gender - Sutarso, Yudi; Setiawan, Djoko Budhi; Suminar, Bagus (Jurnal Manajemen Bisnis, 2023)
Research aims: The paper aims to examine independent value creation (IVC) and its implication on value, trust, and marketing performance (satisfaction and loyalty) in the banking sector in Indonesia. The research model was developed from the existing literature to show the relationship between IVC and marketing performance.Design/Methodology/Approach: A survey design was used in this investigation, and the questionnaire collected study data. The data were analyzed from 385 respondents selected by purposive sampling and taken from bank customers. PLS-SEM analysis was used for hypothesis testing, and multi-group analysis was performed for moderating testing.Research findings: The findings demonstrated a strong positive link between IVC and marketing performance – satisfaction and loyalty. It was also found that learning value and trust partially mediated the relationship. Moreover, gender moderated the relationship between IVC and customer satisfaction and trust.Theoretical contribution/Originality: This study provides an academic contribution to explaining IVC and its role in value, trust, and marketing performance. The impact of IVC is further demonstrated by the role of gender moderation, which contributes to the Service-Dominant Logic (S-D Logic) literature by providing additional context.Practitioner/Policy implication: The study suggests that managers should pay attention to what customers do independently in value creation. They should also alter their perspective of the source of competitive advantage by shifting to customer activities in finding bank services. Furthermore, the impact of IVC on satisfaction and trust needs to consider the role of gender.Research limitation/Implication: The sampling technique limited the generalization of findings, and IVC measurement needs to be explored in future research.